"آليات المفارقة السردية في روايات "مها حسن - فؤاد, نیان نوشیروان; سعيد, نيگار انور حمه (Sulaimani Journal for Humanities, 2021)
This paper, entitled as ‘The Mechanisms of Narrative Parradox in Maha Hasan’s Novels’, is a part of a PhD thesis which is entitled as ‘The Structure of Time and Place in Maha Hasan’s Novels’. In this study, we focused on the techniques of Flashback and Foreshadowing related to time according to the content of the research paper and time displacement within the writer’s novels. She focuses on these techniques for the sake of different themes. With Flashback, the writer focuses on the past events that the characters went through to reveal their truth. Also, with Foreshadowing, the writer focuses on some important time-related techniques, such as: anticipation, dream sequences, and legacy.